Perancangan Sistem Informasi UD. Kauri Abadi Berbasis Web Client Server - Muhtarom, Muhtarom; , Fajar Suryawan, S.T., M.Eng.Sc, Ph.D (2016)
UD.Kauri Abadi are the agency business the field of distributor goods retail and have branch store in some places. UD.Kauri Abadi have constraints on the data collection process transaction most recording transaction data still use manual way or handwriting, so that weaknesses in presentation of transaction data and reports transaction is ineffective and efficient. Design making an application information system UD. Kauri Abadi web-based client server covering analysis needs, collect the data, design systems.Design application was conducted a few stage that is design use case diagram, design scenario system, design database, designer display web, continued the implementation of making an application by using programming php, html, javascript, mysql xampp database, and ajax. Continue to testing stage on the application the system and improvement application until on the outcome in accordance with of design have been made. Application the web being system to display features the menu and form used to management input transaction data covering the action save update remove data, and application to display report transactions. On the application was aimed to ease in management input transaction data and display report fast and easy .In addition application web can walk or accessed more than one client connected on one server database in a computer network